The song folklore of Tozhu Tuvans: collection, publication, research - Tiron, Ekaterina L. (The New Research of Tuva, 2017)
The article explores the history of collecting the Tozhu song folklore, summarizes the current state of research on the topic, and presents the results of author’s investigations conducted since 2003. History of Tozhu Tuvans’ song folklore studies began in 19th century with the materials of P.E. Ostrovskikh and M.I Raikov expeditions. In 1930-1950’s Tuzhu songs had been being collected by the Tuvan intellectuals. Tunes of Tuzhu songs have been first published in 1956 by M.M. Munzuk. The richest data on Tozhu Tuvans’ folklore is stored in the archive of Tuvan Institute of Humanities and Applied Social and Economic Research. The contribution of the Institute’s research fellows included a number of expeditions to Tozhu and recording song folklore at the convents of tale-tellers and singers of Tuva. First audio records of Tozhu Tuvans are dated to 1973. S.I. Vainshtein and Z.B. Chadamba included transcriptions of song texts into their monographs, and Z.K. Kyrgys, transcriptions of texts with melodies. We should also note the significance of works of regional ethnographer T.T. Kushkash, who in 1996 published the song texts transcribed from representatives of Tozhu traditions. A new stage began at the turn of 20th and 21st centuries when Tozhu expeditions resumed under the lead of G.B. Sychenko, a scientist from Novosibirsk. First ethnomusicological studies of Tozhu folklore, which were published in Novosibirsk, were based on the expeditionary data. For the first time ever, a special investigation of Tozhu songs to distinguish between the “yr” and “kozhamyk” genres was conducted by the author. Genres which form the core of song tradition come as a kind of opposition and represent two ways of implementing the lyrical traditions of Tozhu Tuvans. Despite overall typological similarity, each of the genres has high-profile unique features that emerge both on semantic and structural levels. The author analyzed the worldviews of the representatives of traditional culture and the folk terminology they use, defined thematic characteristics of poetic texts, depicted the system of prosody, rhythmosyllabic and pitch organization of folk songs of Tozhu Tuvans. The article also lists the accomplished and future projects aimed at studying, preserving and promoting the unique song folklore of Tozhu Tuvans.